PENGARUH FINANCIAL LITERACY, DEMOGRAPHIC, DAN SOSIO ECONOMIC TERHADAP KEPUTUSAN INVESTASI DI PASAR MODAL SYARIAH DI KOTA BENGKULU - Putra, Rales Eko; Arisandy, Yosy; Arisandi, Debby (JSE: Jurnal Sharia Economica, 2025)
This study aims to analyze the influence of financial literacy, demographic factors, and socio-economic conditions on investment decisions in the Sharia capital market in Bengkulu City. A quantitative approach was employed using multiple linear regression analysis with SPSS version 27. The sample consisted of 99 respondents who are Sharia capital market investors, selected through probability sampling using Slovin’s formula. The results show that financial literacy has a positive and significant effect on investment decisions with a significance value of 0.001 < 0.05. Demographic factors have no significant effect with a significance value of 0.768 > 0.05, while socio-economic factors significantly influence investment decisions with a significance value of 0.017 < 0.05. Simultaneously, the three variables significantly affect investment decisions with an F-value of 36.691 and a significance of 0.000 < 0.05. The R-Square value of 0.733 indicates that 73.3% of the variation in investment decisions is explained by these variables, while the remaining 26.7% is influenced by other factors such as psychological aspects, social media, and macroeconomic conditions